Uji Aktivitas Antibakteri Dan Antijamur Ekstrak Daun Binahong (Anredera cordifolia (Ten) Steenis) - Imran Firman; Iksan Iksan (KOLONI, 2024)
One of the plants that can be used as traditional medicine is binahong leaf (Anredera cordifolia (Ten) Steen). Bioactive subtances from the Binahong plant can help the healing process of disease, research has been carried out on the antibacterial and antifungal activity pf binahong leaf ekstrack (Anredera cordifolia (Ten) Steen). This research is an experimental laboratory aimed at testing the potential antibacterial and antifungal activity of the leaf ekstract of binahong (Anredera cordifolia (Ten) Steen) againts the growth of the bacteria bacillus subtillis s[pan the fungi aspergillus niger. Binahong leaves (Anredera cordifolia (Ten) Steen) Made in the from of a thick ekstrack then carried out phytochemical screening, antibacterial active test using Bacillus Subtillis and shigella sp bacteria also tested for antifungal activity using aspergillus niger fungus. The results showed that the leaf extract of binahong (Anredera cordifola(Ten) Steenins) had antibacterial activity againt bacillus subtillis and shigella sp bacteria at concentrations of 25%, 50%, and 75% by disc method and was in the medium sterong category. And binahong leaf extrac (Anredera cordifolia (Ten) Steen) has antifungal activity againts aspergillus niger at concentrations of 24%, 50%, and 75% by disc method and is in the medium category.